Nest-building Behaviour of the Asian Open Billed Stork Anastomus oscitans, in the Kulik Bird Sanctuary, Raiganj, India - Pramanik, A.K.; Santra, K.B.; Manna, C.K. (Our Nature, 2010)
A field study of the nest-building behaviour in the breeding season of the Asian Open-Billed Stork, Anastomus oscitans, was conducted in the Kulik Bird Sanctuary, Raiganj, Uttar Dinajpur, West Bengal, India. Observations were made throughout one complete breeding season (2007-2008) in the sanctuary. The open-billed stork comes in the last week of June at the Kulik bird sanctuary, stays there for 5 to 6 months and leaves the place in the month of December of every year. From the present observations it was noticed that about 58920 storks came to Kulik during 2008. Various types of behaviour were observed during this particular period. Coming to the Kulik, pairing of the individual storks start and mating display was observed within a day or two. Birds of a pair supplied the nest building materials to form the nest. To give a definite shape to the nest it took about 12-15 days before egg laying. The nesting territory consisted of a semicircle, some times circular and approximately with 30.21 ± 0.12 cm radius. The depth of the nest was about 6.9 ± 0.02 cm. The nest building materials consisted of fragments of old branches of trees, some soft green leaves and grasses. These branches helped in strengthening and the leaves and grasses helped in softening of the nest. During the incubation period both sexes were involved to incubate the eggs. Nest attendance of the breeding birds was continuous during the first 2-months period. From regular observation it was noticed that either of the pair took additional care by spreading their wings during the time of heavy sunshine or heavy rain. The main behavioral patterns examined were aerial displays, mating pattern, nest building, egg laying and incubation pattern, nest defense and nest protection. Diversity of nesting behavior in open-billed stork was pointed out and discussed. Key words: Asian Open-Billed Stork, Kulik Bird Sanctuary, Nest-building behavior DOI: 10.3126/on.v7i1.2552 Our Nature (2009) 7:39-47